2023
DOI: 10.1136/ard-2022-223302
|View full text |Cite
|
Sign up to set email alerts
|

Reducing cardiovascular risk with immunomodulators: a randomised active comparator trial among patients with rheumatoid arthritis

Abstract: ObjectiveRecent large-scale randomised trials demonstrate that immunomodulators reduce cardiovascular (CV) events among the general population. However, it is uncertain whether these effects apply to rheumatoid arthritis (RA) and if certain treatment strategies in RA reduce CV risk to a greater extent.MethodsPatients with active RA despite use of methotrexate were randomly assigned to addition of a tumour necrosis factor (TNF) inhibitor (TNFi) or addition of sulfasalazine and hydroxychloroquine (triple therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 41 publications
1
27
0
1
Order By: Relevance
“…In Solomon et al 33 , vascular in ammation measured by PET-FDG/TC was evaluated in patients randomly assigned to a TNF-α inhibitor vs triple therapy (metothrexate, sulfasalazine and hydroxychloroquine). In this study, both groups improved their disease activity but an association between articular improvement and vascular in ammation was not found.…”
Section: Discussionmentioning
confidence: 99%
“…In Solomon et al 33 , vascular in ammation measured by PET-FDG/TC was evaluated in patients randomly assigned to a TNF-α inhibitor vs triple therapy (metothrexate, sulfasalazine and hydroxychloroquine). In this study, both groups improved their disease activity but an association between articular improvement and vascular in ammation was not found.…”
Section: Discussionmentioning
confidence: 99%
“…Another RCT approach has been to utilize a subclinical CV outcome, which enables measurement of change in an outcome relative to baseline for each therapy. In the recent TARGET RA trial in methotrexate inadequate responders, change in FDG uptake in the aorta and carotid arteries over six months was compared in patients escalated to a TNF inhibitor versus to triple therapy [30 ▪▪ ]. In both groups, FDG uptake decreased by approximately 15% over 6 months and there was no statistically significant difference between treatment groups, thus providing direct proof that reducing vascular inflammation can be accomplished with both a targeted therapy as well as with conventional nontargeted DMARDs.…”
Section: Arterial Disease In Rheumatoid Arthritismentioning
confidence: 99%
“…A systematic review of RCTs and observational studies in RA found that TNFi use was associated with a reduced risk of all MACE. In a recent RCT, Solomon et al [9 ▪ ], randomized patients with active RA despite use of MTX to either addition of a TNFi or triple therapy for 24 weeks and monitored arterial inflammation with serial PET scans. Both arms showed similar clinically important improvements in vascular inflammation.…”
Section: Safety Data Of Various Biologic Disease Modifying Antirheuma...mentioning
confidence: 99%